Expert Versus Novice Interrater Reliability and Criterion Validity of the Landing Error Scoring System - Onate, James (J Sport Rehabil, 2010)
CONTEXT: A clinical assessment tool that would allow for efficient large-group screening is needed to identify individuals potentially at risk for anterior cruciate ligament (ACL) injury. OBJECTIVE: To assess the criterion validity of a jump-landing assessment tool compared with 3-dimensional (3D) motion analysis and evaluate interrater reliability across an expert vs novice rater using the Landing Error Scoring System (LESS). DESIGN: Validity protocol. SETTING: Controlled, laboratory. PARTICIPANTS: Nineteen female (age 19.58 ± .84 y, height 1.67 ± .05 m, mass 63.66 ± 10.11 kg) college soccer athletes volunteered. MAIN OUTCOME MEASUREMENT: Interrater reliability between expert rater (5 y LESS experience) vs novice rater (no LESS experience). LESS scores across 13 items and total score. 3D lower extremity kinematics were reduced to dichotomous values to match LESS items. INTERVENTIONS: Participants performed drop-box landings from a 30-cm height with standard video-camera and 3D kinematic assessment. RESULTS: Intrarater item reliability, assessed by kappa correlation, between novice and experienced LESS raters ranged from moderate to excellent (κ = .459–.875). Overall LESS score, assessed by intraclass correlation coefficient, was excellent (ICC(2,1) = .835, P < .001). Statistically significant phi correlation (P < .05) was found between rater and 3D scores for knee-valgus range of motion; however, percent agreement between expert rater and 3D scores revealed excellent agreement (range of 84–100%) for ankle flexion at initial contact, knee-flexion range of motion, trunk flexion at maximum knee flexion, and foot position at initial contact for both external and internal rotation of tibia. Moderate agreement was found between rater and 3D scores for trunk flexion at initial contact, stance width less than shoulder width, knee valgus at initial contact, and knee-valgus range of motion. CONCLUSIONS: Our findings support moderate to excellent validity and excellent expert vs novice interrater reliability of the LESS to accurately assess 3D kinematic motion patterns. Future research should evaluate the efficacy of the LESS to assess individuals at risk for ACL injury.